The Influence Of Muthawif (Tour Leader) Competence On The Satisfaction Of Umrah Pilgrims At PT. Arafah Mulia Insani North Jakarta - Ayu Nadia Aini; Imam Ardiansyah (Pusat Publikasi Nusantara, 2025)
This study focuses on the important role of muthawif (tour guide) in accompanying Umrah pilgrims, both technically and spiritually. The purpose of this study was to analyze how much influence muthawif competence has on Umrah pilgrim satisfaction at PT. Arafah Mulia Insani located in North Jakarta. Muthawif competence in this study includes 6 dimensions namely knowledge, understanding, values, skills, attitudes, and interests. The method used in this study is a quantitative approach with a descriptive- associative technique. A total of 30 respondents were selected through a purposive sampling method. Data were collected using a questionnaire with a Likert scale, and data analysis was carried out using 10 tests with the help of SPSS. The results of the study indicate that muthawif competence has a significant influence on pilgrim satisfaction, both separately and simultaneously. The dimensions of knowledge and skills are the main factors influencing pilgrim satisfaction. The researcher suggests that Umrah organizers continue to improve training and evaluation of muthawifs on an ongoing basis. Further research is expected to involve more respondents and more diverse variables.